Implementasi Functional Requirement Bibliographic Resources (FRBR) dan Dampaknya pada Katalog Modern - Handisa, Rattah Pinusa (STAIN Ponorogo, 2017)
A dynamic change in the collection management system encourages the libraries to re-new their cataloguing system. Functional Requirement Bibliographic Resources (FRBR) is an alternative cataloguing system to replace Anglo American Cataloguing Rules. International Federation of Library Association (IFLA) developed FRBR in 1997 and the FRBR stimulated the discussions among the librarians and their stakeholders. The purpose of this essay is to discuss the contribution FRBR for modern cataloguing and to argue the importance applying FRBR in the modern catalogues. FRBR has a positive contribution for developing the metadata. FRBR overcomes the interoperability issue by providing a standard of metadata. In addition, FRBR improves the accuracy in the information retrieval by using entity relationships. Meanwhile, there was an assumption that the financial and human development issues would interrupt the implementation of FRBR. However, applying FRBR gives more advantages rather than its drawbacks. Firstly, FRBR reduces the workload in the cataloguing process by avoiding data redundancies. Secondly, FRBR reduces the operational expense. Thirdly, FRBR has an ability to connect the complex metadata structure by using Resource Definition Framework (RFD) and Universal Resources Identifier (URI). Both RFD and URI features improve the accuracy of search engine for digital objects. In conclusion, FRBR gives a positive contribution for modern cataloguing due to effectivity in the retrieving information and efficiency in the cataloguing process.Â